Adopting Cryptocurrency Apps from a Sharia Perspective: The Readiness of Generation Z Muslims in the Digital Technology Era - Hanna, Siti; Masruroh, Siti Ummi; Amrin, Amrin; Ningrum, Dewi Aprilia; Suseno, Hendra Bayu (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
The development of Web 3.0 technology has driven the birth of various digital innovations, including cryptocurrency and blockchain-based financial applications. This phenomenon affects the pattern of technology adoption by Generation Z Muslims, who are known to be adaptive to technology but still bound by religious values. This study aims to analyze the readiness of Generation Z Muslims to adopt cryptocurrency applications from a Sharia law perspective and to evaluate their understanding of the provisions of fiqh muamalah in a digital context. The methodology used is a qualitative approach with literature study and document analysis. The study results show that although most Generation Z have high digital skills, there is still a gap in understanding regarding the legal status of cryptocurrency in Islam. Based on the 2021 DSN MUI fatwa, cryptocurrency as a currency is considered haram because it contains elements of gharar and dharar. Still, it can be accepted as a digital asset with clear underlying assets and real benefits. This study concludes that Sharia financial literacy and digital literacy need to be improved simultaneously to support adopting financial technology based on Sharia principles. These findings contribute to developing a sustainable, inclusive, and adaptive digital sharia financial ecosystem to the dynamics of Web 3.0 technology.